Synthetic Biology, Genome Editing, and the Risk of Bioterrorism. - Ahteensuu, Marko (Science & Engineering Ethics, 2017)
The SynBioSecurity argument says that synthetic biology introduces new risks of intentional misuse of synthetic pathogens and that, therefore, there is a need for extra regulations and oversight. This paper provides an analysis of the argument, sets forth a new version of it, and identifies three developments that raise biosecurity risks compared to the situation earlier. The developments include (1) a spread of the required know-how, (2) improved availability of the techniques, instruments and biological parts, and (3) new technical possibilities such as 'resurrecting' disappeared pathogens. It is first shown that the general argument from SynBioSecurity needs to be qualified and that many improvements to biosecurity have already been implemented, most notably in the United States. Second, I suggest a new strain of the argument: the situation that most branches of synthetic biology fall under the gene technology regulation in the European Union and that this regulation in its current form does not adequately address SynBioSecurity risks together provide a weighty reason to review and possibly refine the legislation as well as the supervisory practices. Ethically speaking, the rise in the relative risk of bioterrorism brings to the fore new extrinsic issues.